BUDAYA ORGANISASI: PENGARUHNYA TERHADAP KINERJA MELALUI KEUNGGULAN BERSAING KOPERASI DI JAWA BARAT - Dyahrini, Wien (BISMA: Jurnal Bisnis dan Manajemen, 2019)
This study aims to analyze the influence of organizational culture on performance through competitive advantage in the Cooperatives in West Java Province. The sample consisted of 370 active cooperatives in the regencies and cities in West Java Province, which was collected by applying a purposive cluster proportional sampling technique. Research data were analyzed using SEM. The results showed that organizational culture influenced performance through cooperative’s competitive advantage. This finding implied that a strong organizational culture will create a better competitive advantage that will finally give a positive effect on the improved performance of cooperatives in West Java Province. Keywords: organizational culture, competitive advantage, performance, cooperatives